Indonesia : new haven for cybercriminals? - Senol Yilmaz (2014)
Indonesia has been identified as a major source of malicious Internet traffic. A close examination, however, reveals that such traffic may not originate in Indonesia. More likely, Indonesian networks are exploited by outside e-criminals.